An N-of-1 Feasibility Study of Homeopathic Treatment for Fatigue in Patients Receiving Chemotherapy - Brulé, David; Balon, Jeffrey; Zhao, Linlu; Seely, Dugald (Homeopathy, 2018)
Background Cancer-related fatigue has been described as a subjective feeling of physical, emotional, and/or cognitive tiredness. Homeopathy has been widely used to treat side effects of chemotherapy. The n-of-1 design is a single-patient trial method to study a clinical condition that is either short lived and reversible or is chronic and stable. The n-of-1 design requires a washout/reset period. The feasibility of performing an n-of-1 study in homeopathy has not previously been tested.Methods A feasibility n-of-1 trial of individualized homeopathic treatment for fatigue in a single adult undergoing chemotherapy administered periodically was performed. For each matched pair of treatments, the participant was randomly allocated either placebo or verum for the period between treatments. For the subsequent treatment period, the opposite allocation was given. Participant and practitioner were blinded to the allocation. Ongoing conventional treatments were permitted. The ability to recruit and retain was monitored and changes in fatigue and quality of life were measured using two validated outcome measures.Results Sixty-eight patients were assessed between February 2014 and February 2015. Four patients were eligible for the study and one consented to participate. The participant enrolled in the study for six cycles of chemotherapy and completed all treatment and outcome measures. There was no improvement under homeopathic treatment compared to placebo. There were multiple confounding events such as conventional medication changes and an adverse event unrelated to therapy.Conclusion Adequate recruitment was not feasible in this setting. The n-of-1 study design is feasible in this population from the perspective of the ability to complete the trial. No conclusion on the efficacy of homeopathy for this individual can be made. It is unclear as to whether multiple treatments of chemotherapy would be an appropriate clinical situation in which to apply the n-of-1 trial methodology. Future studies should pilot adaptations to this study design.
Keywords: homeopathy; n-of-1 study; chemotherapy; complementary and alternative medicine